The Impact of Geological Processes on the Location of Shahrake Firouzeh, a Prehistoric Site from NE Iran. (18th June 2019) - Rezaei, Mohammad Hossein; Basafa, Hassan
Today, geoarchaeological studies have turned into a useful tool in archaeological studies to explain ancient Quaternary environments. This paper examines the impact of environmental and geological conditions on location of Late Bronze Age Shahrake Firouzeh settlement. Shahrake Firouzeh settlement is located northwest of Neyshabur County with an average altitude of 1250 meters above sea level and 36°12′48″N 58°47′45″E coordinates. At the same time, geological and sedimentation outcrops based on research method of systemic comparative analysis have been used to examine the impact of these conditions on location and/or destruction of this site. Evidence suggests the occurrence of a massive climatic catastrophe in the second millennium BC in Shahrake Firouzeh site, which buried the entire plain under alluvial deposits in a short period of time. These developments occurred concurrent with the establishment of the settlement and a short while after abandonment of it. Due to the vast area of Shahrake Firouzeh, lack of water extraction techniques of qanāt and deep well digging, the conveyance of water from Somea basin through canals can be deemed. Location of Shahrake Firouzeh on floodplain deposits as well as minimum distance from the watershed outlet due to water conveyance indicates the agricultural origin of this site.